PENGEMBANGAN GAME EDUKASI 2D MATA PELAJARAN IPA MENGGUNAKAN UNITY BERBASIS MOBILE - Prayudha, Ilham Teguh; Chotijah, Umi (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
Technological advances have had a great influence in various areas of life, including in the digital entertainment industry such as video games. There are many children who are more interested in playing games than learning, which can result in a decrease in interest in learning academic activities. Therefore, finding an effective method to balance children's interest in learning by playing games is very important. One solution is to create educational games that provide a fun and interactive learning experience. This research aims to develop an educational game that can help children play while learning. The development of 2D educational games for science subjects uses Unity Engine and MDLC (Multimedia Development Life Cycle) as development methods. From the results of the discussion, the creation of the game was successful. Based on the results of application testing that has been carried out on educational games, all components of this game function properly and there are no problems. In addition, beta testing shows that this educational game has been proven to be able to increase students' interest in learning